In-service English Teachers' Barriers in Integrating Technology in EFL Classes: A Case Study at English Teachers' Forum of Majalengka - Eka Nurhidayat; Januarius Mujiyanto; Issy Yuliasri; Rudi Hartono (International Conference on Science, Education, and Technology, 2022)
During the post-pandemic period triggered by COVID-19, integrating technology into English as a foreign language (EFL) classes significantly impacted the teaching and learning process. As a result, many English teachers struggle to integrate technology into their classrooms. This study examined the difficulties encountered by in-service English teachers when integrating technology into class. The participants were ten English teachers currently employed at the English teachers’ forum in Majalengka. In-service English teachers' experiences integrating technology into EFL Classes are covered via the descriptive qualitative method. Questionnaires and interviews are the primary methods utilized in the data collection process. This study will overview in-service teachers' obstacles in EFL classes.